Cs+ Adsorption and Pyrolytic Volume Reduction Performance of KR-01 Mixed Ion Exchange Resin - Weilei GUO; Hongyi GAO; Jinchi MAO; Renliang YUE; Haidi LIU (Journal of Isotopes)
Cesium-137 (137Cs) is one of the most common radioactive substances in nuclear reactor wastewater, developing efficient Cs+ adsorbing materials is of paramount importance for sustainable development of nuclear energy, human health protection, and environmental conservation. The company has developed a KR-01 mixed ion exchange resin by blending the synthesized cation and anion exchange resins in a 1:1.8 mass ratio. This study systematically investigated the Cs+ adsorption performance of KR-01 mixed ion exchange resin, focusing on the effects of factors such as adsorption time, resin dosage, and pH on the adsorption efficiency. The adsorption kinetics and adsorption isotherm processes of Cs+ on the resin were also studied. Under the conditions of 25 ℃ and pH 6.0, the static saturation adsorption capacity and adsorption rate of the resin reach 98.159 mg/mL and 99.960%. The study showed that the pseudo-first-order kinetic model provided a high coefficient of determination (R2=0.997), indicating the Cs+ adsorption process on the KR-01 resin was diffusion-controlled, involving a rapid initial adsorption stage followed by a slower adsorption stage. Within a certain concentration range, the Cs+ adsorption on the KR-01 resin followed both Langmuir and Freundlich adsorption isotherms, with R2 values exceeding 0.940. However, the Langmuir equation more accurately described the ion exchange adsorption process, highlighting the dominance of the monolayer adsorption mechanism described by the Langmuir model. After pyrolysis at 900 ℃, the residual amount of resin is around 48.970%, and Cs+ is virtually undetectable in the pyrolytic volatile gases, achieving efficient volume reduction and stable disposal of the waste resin. The Cs+ adsorption capacity and pyrolytic volume reduction performance of KR-01 resin are superior to representative commercially available resins abroad.